As características clínicas e ultrassonográficas dos nódulos tireoidianos com citologia Bethesda III ou IV podem refinar a indicação de testes de diagnóstico molecular? - Camila Teixeira Costa Barbosa (2022)
Introduction: With the increase in the diagnosis of thyroid nodules, it is necessary to use tools that help in the best definition, regarding the suspicion of malignancy or benignity, to avoid diagnostic surgeries in nodules with indeterminate cytology. The means available for the investigation of these nodules are the clinical history, ultrasound and cytological characteristics and, currently, molecular tests, which play an important role in the prediction of malignancy, but are not very accessible due to their high cost. Objective: To verify if there is an association between clinical and ultrasonographic characteristics with the risk of malignancy in patients with thyroid nodules and indeterminate Bethesda III and IV cytology, and if these characteristics can help in the indication of molecular testing to improve surgical indication. Method: Analysis of the association of malignancy of Bethesda III or Bethesda IV thyroid nodules with age variables <55 or ≥ 55 years, sex, family history of thyroid cancer, history of irradiation, nodule size, and ACR TI-RADS and ATA 2015 classification. analyzed 62 thyroid nodules from 62 participants who underwent thyroidectomy. Results: 87.1% (54/62) were female, 74.2% were <55 years, 95.2% had no family history of thyroid cancer, 56.5% had nodules <2 cm, 62.9% were Bethesda IV and 69.4% were ACR TI-RADS 4. Thirty-two patients had thyroid carcinomas and 30 had benign histology. The sample's characteristics related to sex, age, family history and nodule size did not show any statistical difference in terms of benignity and malignancy of the nodules in the sample. Among all factors associated with malignancy, only ACRTIRADS 5 ultrasonographic classification and Bethesda category III with nuclear atypia showed a significant association. Conclusion: Bethesda III thyroid nodules without nuclear atypia and Bethesda IV thyroid nodules with intermediate sonographic characteristics for malignancy (ACR TIRADS 3 or 4), corresponding to 71%, 44/62 nodules in the study sample, would benefit from available molecular diagnostic tests, since among the clinical-anatomopathological and ultrasonographic characteristics analyzed, only the ultrasonographic classification of high risk for malignancy (ACR TIRADS 5) and Bethesda III cytology with nuclear atypia were able to indicate malignancy.